Sustentabilidade e competitividade na cadeia logística: redução de emissões de gases de efeito estufa com o uso do modal de transporte cabotagem: estudo de caso - Barbosa, Luciane Pereira (2018)
This work analyzes and propagates the sustainability of cabotage transport in the logistics operation of a home appliances manufacturing company. The research method was a case study, unique and holistic, about cabotage transport and its impacts on CO2 emissions in the logistics chain of the company's operations in Brazil. The continental dimensions of this country lead to a significant challenge in the logistics chain to meet the demands of customers, while quickly maintaining its competitiveness and safety. In this context, starting in 2015, the company intensified the use of cabotage shipping in order to reduce insurance costs and avoid problems with cargo theft. Nevertheless, a positive externality went unnoticed: the reduction in CO2 emissions due to the use of this modal. One of the company's sustainability goals is to minimize its climate impact by preventing the release of 25 million tonnes of carbon dioxide and its equivalents (CO2e) over 15 years between 2005 and 2020, and one way is to promote the use of more efficient transport modes. In the review of the literature, it has shown that CO2 emissions by road transport can be up to 10 times greater than maritime transport for the same volume of transported product (SCHMIED and KNÖRR, 2012). Therefore, this research was carried out through the exploratory analysis on the data of shipments made by the company from January/2015 to August/2018 and calculation of the impact on CO2 emissions of the respective shipments, adopting the method proposed in CEN- EN 16258 - 'Methodology for calculating and reporting energy consumption and greenhouse gas emissions from transport services'. This paper aims to contribute to the study on sustainability in logistics chains and to bring greater clarity to managers about the positive impacts in competitiveness and environment when adopting an alternative mode of transport to the traditional road transport.